Evaluation of Thyroid Dysfunction among Libyan Patients with Type-2 Diabetes Mellitus - Zainab EL Mabrouk,; Abd Al Naser Mohammed,; Fauzia Mohamed,; Habiba El Jaafari,; Nacereddine Toumi, (AlQalam Journal of Medical and Applied Sciences, 2024)
Thyroid disorders are more common in people with diabetes compared to the general population. This study aimed to evaluate the prevalence of thyroid disorders in Libyan patients with type 2 diabetes mellitus (T2DM) and the association between thyroid dysfunction and T2DM parameters. The current study included a total of 50 participants: 40 with T2DM, and 10 healthy volunteers. They were divided into three groups: G1 (10 healthy controls), G2 (30 patients with T2DM [DM]), and group 3 [10 patients with T2DM and thyroid dysfunction (DM+TD)]. The average age of control and patients was 33.1±10.9 years and 55.3±12.8 years, respectively. The diabetes profile (FBS, RBS, and HbA1c), and thyroid profile (TSH, FT3, and FT4) of each participant were assessed. The levels of FBG, RBS, and HbA1c showed a highly significant (P=0.000) increase in the DM and DM+TD groups compared to the healthy control group. Additionally, the findings indicated that the majority of the participants with diabetes (75%) had normal thyroid function, while 25% had thyroid disorders., Among the patients with thyroid disorders, 10% had subclinical hypothyroidism, 7.5% nonthyroidal illness syndrome (NITS), and 7.5% exhibited high levels of TSH, FT4, and FT3.,. The prevalence of thyroid disorders was higher in women (22.5%) than in men (2.5%). None of the diabetic patients showed hyperthyroidism in this study. The study concluded that 25% of patients with type 2 diabetes mellitus had a thyroid disorder, and subclinical hypothyroidism was more prevalent. Also, the current study showed that female gender and family history of thyroid disorders are important risk factors. تعد اضطرابات الغدة الدرقية أكثر شيوعا لدى مرضى السكري مقارنة بعامة الناس. تهدف هذه الدراسة الى تقييم مدى انتشار اضطرابات الغدة الدرقية لدى المرضى الليبيين المصابين بداء السكري من النوع الثاني T2DM)) وكذلك العلاقة بين خلل الغدة الدرقية ومؤشرات T2DM. شملت الدراسة الحالية 50 مشارك: 40 مصابا ﺑT2DM و 10 متطوعين أصحاء. تم تقسيمهم الى ثلاث مجموعات: المجموعة الاولى (10 أصحاء) ، المجموعة الثانية (30 مريضأ يعانون من مرض السكري فقط DM) والمجموعة الثالثة (10 مرضى يعانون من مرض السكري وخلل في الغدة الدرقية DM+TD). كان متوسط عمر الاصحاء والمرضى 33.1 ± 10.9 و 55.3 ± 12.8 سنة على التوالي. تم تقييم مؤشرات مرض السكري (HbA1c, RBS, FBS) ومؤشرات الغدة الدرقية (TSH, FT3, FT4) لكل مشارك. أظهرت نتائج الدراسة ان مستويات HbA1c, RBS, FBS كان مرتفعا (P=0.000) في مجموعتي DM و DM+TD مقارنة بمجموعة الأصحاء. بالإضافة إلى ذلك، أشارت النتائج الى أن غالبية المشاركين المصابين بداء السكري (75%) لديهم وظائف الغدة الدرقية طبيعية، بينما كان 25% يعانون من اضطرابات الغدة الدرقية. المرضى الذين لديهم خلل في الغدة الدرقية كان منهم 10% يعانون من قصور الغدة الدرقية تحت السريري ، و 7.5% يعانون من متلازمة NITS ، و 7.5% لديهم مستويات عالية من هرمونات .TSH, FT3, FT4 وكان معدل انتشار اضطرابات الغدة الدرقية أعلى لدى النساء (22.5%) مقارنة بالرجال (2.5%) . لم يظهر أي من مرضى السكري فرط نشاط الغدة الدرقية في هذه الدراسة. خلصت الدراسة الى أن 25% من من مرضى السكري من النوع الثاني يعانون من اضطراب الغدة الدرقية، وأن قصور الغدة الدرقية تحت السريري كان أكثر انتشارا. كما أظهرت أن الإناث والتاريخ العائلي لاضطرابات الغدة الدرقية من عوامل الخطر المهمة